Information Used to Decide on Retreatment of Exudative Age-Related Macular Degeneration with anti-VEGF in Clinical Practice. Issue 1 (January 2013) - Manousaridis, Kleanthis; Manjunath, Vina; Talks, James
Purpose: To record the information used in order to make a retreatment decision in patients with exudative age-related macular degeneration (AMD) and to assess if an optical coherence tomography (OCT)–only follow-up clinic would suffice. Methods: Two hundred patients under treatment with intravitreal anti–vascular endothelial growth factor injections (anti-VEGF) for exudative AMD were included. Each patient had previously received at least 3 intravitreal anti-VEGF injections (loading dose) (range 3–24 injections). Clinicians seeing the patients beyond the third injection were asked to document the criteria used to make a retreatment decision. Results: Overall, in 171 (85.5%) cases the retreatment decision was based on OCT findings of intraretinal or subretinal fluid alone. Diagnosis of recurrence requiring treatment would have been missed in 12 cases (6%), if OCT-only data had been used and funduscopy or visual function criteria had been omitted. Decision was based solely on functional criteria in only 2% of the cases. The retreatment decision was based on evaluation of morphologic funduscopic or OCT criteria in 187 (93.5%) cases. Conclusions: With the increasing number of patients having follow-up after anti- VEGF treatment, efficient systems of follow-up are required. Although most retreatment decisions could have been made by qualitative assessment of OCT images alone, the examination has considerable limitations. Optical coherence tomography in combination with color fundus photography could serve as screening tools for a rational implementation of other invasive imaging techniques such as fundus fluorescein angiography and indocyanine green angiography in decision-making.